SALSOLA RICHTERI (MOQ.) KAREL EX LITV. HÁM SALSOLA PALETZKIANA LITV.LER–TIYKARǴÍ FITOMELIORANT ÓSIMLIKLER - Karlıbayeva, M.A.; Baltabaev, M.T. (SCIENCE and SOCIETY, 2023)
The article presents new information about phytomeliorative works in Aralkum. It is expedient to use these plants together with saxaul in phytomeliorative works in the arid zone of the Aral Sea.